Case Report: Recurrent meningioma with multiple metastases - Zhou, Juyue; Du, Zhonghai (Frontiers in Oncology, 2023)
Post-surgery recurrence of meningiomas with multiple extracranial metastases is rare.Currently, information on extracranial metastases is limited, and no clear predictors and standardized treatment protocols can be applied clinically. Herein, we report a case of meningioma that recurred after two surgeries and had multiple distant metastases.Computed tomography revealed multiple enlarged lymph nodes in the para-aortic arch, left lower lung region, retroperitoneum, and abdominopelvic region, as well as soft tissue mass-like lesions under the liver capsule in the right lobe of the liver. Magnetic resonance imaging showed space-occupying lesions under the cranial plate of the left parietal lobe. Tissue biopsy confirmed the diagnosis of recurrent meningioma with extracranial metastases. Immune checkpoint inhibitors and anti-angiogenic drugs were administered. After two treatment cycles, the patient's clinical symptoms were significantly relieved, and the imaging assessment confirmed a stable disease. Although it did not meet our expectations, this combination therapy still demonstrated a possible benefit in improving meningioma patients' survival and quality of life. In this report, along with the case, we also review the relevant literature on the subject and discuss the associated risk factors and treatment options.